Phenol-Soluble Modulin α Peptide Toxins from Aggressive Staphylococcus aureus Induce Rapid Formation of Neutrophil Extracellular Traps through a Reactive Oxygen Species-Independent Pathway - Björnsdottir, Halla; Dahlstrand Rudin, Agnes; Klose, Felix P.; Elmwall, Jonas; Welin, Amanda; Stylianou, Marios; Christenson, Karin; Urban, Constantin F.; Forsman, Huamei; Dahlgren, Claes; Karlsson, Anna; Bylund, Johan (Frontiers in Immunology, 2017)
Neutrophils have the ability to capture and kill microbes extracellularly through the formation of neutrophil extracellular traps (NETs). These are DNA and protein structures that neutrophils release extracellularly and are believed to function as a defense mechanism against microbes. The classic NET formation process, triggered by, e.g., bacteria, fungi, or by direct stimulation of protein kinase C through phorbol myristate acetate, is an active process that takes several hours and relies on the production of reactive oxygen species (ROS) that are further modified by myeloperoxidase (MPO). We show here that NET-like structures can also be formed by neutrophils after interaction with phenol-soluble modulin α (PSMα) that are cytotoxic membrane-disturbing peptides, secreted from community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA). The PSMα-induced NETs contained the typical protein markers and were able to capture microbes. The PSMα-induced NET structures were disintegrated upon prolonged exposure to DNase-positive S. aureus but not on exposure to DNase-negative Candida albicans. Opposed to classic NETosis, PSMα-triggered NET formation occurred very rapidly, independently of ROS or MPO, and was also manifest at 4°C. These data indicate that rapid NETs release may result from cytotoxic membrane disturbance by PSMα peptides, a process that may be of importance for CA-MRSA virulence.